CODE-MIXING IN DIALOGUES AS SEEN IN ALICE COMIC BY ANGELLINA - Farahsani, Yashinta; Rini, Ika Puspita; Jaya, Patria Handung (Faculty of Humanities, Diponegoro University, 2019)
Since English has become international language, Indonesian people prefer to mix their language using Indonesian and English rather than Indonesian and their mother tongue language. Indonesian comics are also showing this phenomenon. One of Indonesian comics which uses code-mixing in its dialogues is Alice by Angellina. Most of the dialogues in Alice use Indonesian-English code-mixing, besides the characters’ names are also use Western names, instead of Indonesian names. The study focused on determining the types of code mixing: insertions, alternations, congruent lexicalizations (dialect) and the forms of words in the process of word-formation (such as noun, verb, adjective, phrase, and sentences). The tendency in using the code mixing is because some words have been used so often in the people’s daily conversation in showing the emotions and sense.